Discovery of pyrimidine-tethered benzothiazole derivatives as novel anti-tubercular agents towards multi- and extensively drug resistant Mycobacterium tuberculosis - Loah R. Hemeda; Mahmoud A. El Hassab; Mohamed A. Abdelgawad; Eman F. Khaleel; Marwa M. Abdel-Aziz; Faizah A. Binjubair; Sara T. Al-Rashood; Wagdy M. Eldehna; Mohamed K. El-Ashrey (Taylor & Francis Group, 2023)
In this study, new benzothiazole-pyrimidine hybrids (5a-c, 6, 7a-f, and 8-15) were designed and synthesised. Two different functionalities on the pyrimidine moiety of lead compound 4 were subjected to a variety of chemical changes with the goal of creating various functionalities and cyclisation to further elucidate the target structures. The potency of the new molecules was tested against different tuberculosis (TB) strains. The results indicated that compounds 5c, 5b, 12, and 15 (MIC = 0.24-0.98 µg/mL) are highly active against the first-line drug-sensitive strain of Mycobacterium tuberculosis (ATCC 25177). Thereafter, the anti-tubercular activity was evaluated against the two drug-resistant TB strains; ATCC 35822 and RCMB 2674, where, many compounds exhibited good activity with MIC = 0.98-62.5 3 µg/mL and 3.9-62.5 µg/mL, respectively. Compounds 5c and 15 having the highest anti-tubercular efficiency towards sensitive strain, displayed the best activity for the resistant strains by showing the MIC = 0.98 and 1.95 µg/mL for MDR TB, and showing the MIC = 3.9 and 7.81 µg/mL for XDR TB, consecutively. Finally, molecular docking studies were performed for the two most active compounds 5c and 15 to explore their enzymatic inhibitory activities.